Robot perception for object handling - Seah, Brian Yee Chuen (Nanyang Technological University, 2020)
Robotics is an interdisciplinary field of Engineering that has changed the way we work and live. This field of Engineering is becoming even more popular with the rise of Industry 4.0 or the fourth industrial revolution which aims towards the automation of factories, using technologies such as artificial intelligence (AI) and robotic manipulators. This project aims to combine these two technologies and is a continuation of a project started in Panasonic R&D Center Singapore. The final goal of this project is to create a sorting system with the Universal Robots UR5 robotic manipulator and the Intel Realsense D435i depth camera. The project will be split up into 3 phases. The first phase will be the creation of a simulated environment and a motion controller using Robot Operating System (ROS) for the UR5 robot. The second phase will be to create a computer vision system based on Convolutional Neural Networks (CNN) to detect objects for picking and sorting. The third and final phase will see the completion of the system by interfacing both the motion controller system with the computer vision system.